2022
DOI: 10.1186/s12866-022-02493-2
|View full text |Cite
|
Sign up to set email alerts
|

LysX2 is a Mycobacterium tuberculosis membrane protein with an extracytoplasmic MprF-like domain

Abstract: Background Aminoacyl-phosphatidylglycerol (aaPG) synthases are bacterial enzymes that usually catalyze transfer of aminoacyl residues to the plasma membrane phospholipid phosphatidylglycerol (PG). The result is introduction of positive charges onto the cytoplasmic membrane, yielding reduced affinity towards cationic antimicrobial peptides, and increased resistance to acidic environments. Therefore, these enzymes represent an important defense mechanism for many pathogens, including Staphylococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The deletion of lysX leads to disruptions in membrane potential, growth impairment, and defects in intracellular replication [500]. Additionally, another LysX orthologue, named LysX2, is exclusive to pathogenic mycobacteria and has been demonstrated to decrease the surface negative charge under acidic conditions, enhance bacterial cell viability at lethal pH levels, and hinder biofilm formation [502].…”
Section: Role Of the Cytoplasmic Membrane Phospholipids And Their Mod...mentioning
confidence: 99%
“…The deletion of lysX leads to disruptions in membrane potential, growth impairment, and defects in intracellular replication [500]. Additionally, another LysX orthologue, named LysX2, is exclusive to pathogenic mycobacteria and has been demonstrated to decrease the surface negative charge under acidic conditions, enhance bacterial cell viability at lethal pH levels, and hinder biofilm formation [502].…”
Section: Role Of the Cytoplasmic Membrane Phospholipids And Their Mod...mentioning
confidence: 99%
“…Recently, Boldrin and colleagues ( 164 ) reported that lysX2 is a prototype of a new class within the MprF-like protein family that likely enhances the survival of pathogenic species through its catalytic domain, which is exposed to the extra cytoplasmic side of the cell membrane and is required to decrease the negative charge on the bacterial surface. LysX2 expression in M. smegmatis increased cell resistance to HBD-2 and sodium nitrite, improved cell viability, and delayed biofilm formation in an acidic pH environment.…”
Section: Tuberculosis Strikes Back and Resistance To Amps: W...mentioning
confidence: 99%
“…The authors reported lysX2 orthologues in major human pathogens and in rapidly growing mycobacteria frequently associated with human infections, but not in environmental and nonpathogenic mycobacteria. Although the Mtb proteome presents a protein with 100% identity compared to the reported lysX2 prototype, it has not been reported whether it has the same functions as lysX ( 164 ).…”
Section: Tuberculosis Strikes Back and Resistance To Amps: W...mentioning
confidence: 99%